Laparoscopic hysterectomies for large uteri - Kai-Yun Wu; Srithean Lertvikool; Kuan-Gen Huang; Hsuan Su; Chih-Feng Yen; Chyi-Long Lee (Elsevier, 2011)
Laparoscopic hysterectomies increase recently due to several advantages of minimally invasive surgery. Controversy exists for laparoscopic hysterectomies for large uteri weighing >500 g because some reports show increased complications and morbidities and high laparoconversion rate in the past. With familiarity of laparoscopic procedures and progress in surgical techniques, the issue should be discussed and reviewed by evidence again. Hence, we conducted a systematic review of laparoscopic hysterectomies for large uteri.